PENGGUNAAN METODE COLLEGE BALL UNTUK PENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PADA MATERI PERBANDINGAN - Theresia Cesita Melania Jue; Maria Fatima Mei; Ariswan Usman Aje (Program Studi Pendidikan Matematika, 2023)
The objectives of this research are 1) To determine students' learning activities when the college ball learning method is applied using snakes and ladders media in comparative material; 2) To find out student learning outcomes when the college ball learning method is applied using snake and ladder media. The type of research used is Classroom Action Research (PTK). PTK is carried out in two cycles where each cycle is held in two meetings. Data collection techniques are tests of learning outcomes and observation of learning implementation. Data analysis techniques use qualitative data analysis techniques and quantitative data. The research results show that using the college ball learning method using snakes and ladders as a medium can increase student activity and learning outcomes. This can be seen in the first cycle, the average value of student learning outcomes was 65.8% and the average value of student activity observations was 65%. In cycle II, the average value of student learning outcomes was 79.3% and the average value of student activities was 84%. Based on the research that has been carried out, the research results of the college ball learning method using snakes and ladders media can be said to increase student activity and learning outcomes.